IMF Survey, Volume 32, Issue 12. (IMF Survey; IMF Survey ;, 2003)
IMF Deputy Managing Director Eduardo Aninat leaves the IMF on July 1 to return to Chile, where he was Finance Minister from 1994-1999. Aninat joined the IMF's four-member management team in December 1999, with broad responsibilities in running the IMF-including overseeing the launching of a major technical assistance initiative in Africa. He talks with Laura Wallace about the late May opening of the West Africa Regional Technical Assistance Center (West AFRITAC) in Mali (see article below), seven months after the opening of a similar center in East Africa.